The Impact of Breast Cancer Treatment Delays on Survival Among South African Women. (31st January 2022) - Pumpalova, Yoanna S; Ayeni, Oluwatosin A; Chen, Wenlong Carl; Buccimazza, Ines; Cačala, Sharon; Stopforth, Laura W; Farrow, Hayley A; Mapanga, Witness; Nietz, Sarah; Phakathi, Boitumelo; Joffe, Maureen; McCormack, Valerie; et al.
Abstract: Background: In high-income settings, delays from breast cancer (BC) diagnosis to initial treatment worsen overall survival (OS). We examined how time to BC treatment initiation (TTI) impacts OS in South Africa (SA). Methods: We evaluated women enrolled in the South African BC and HIV Outcomes study between July 1, 2015 and June 30, 2019, selecting women with stages I-III BC who received surgery and chemotherapy. We constructed a linear regression model estimating the impact of sociodemographic and clinical factors on TTI and separate multivariable Cox proportional hazard models by first treatment (surgery and neoadjuvant chemotherapy (NAC)) assessing the effect of TTI (in 30-day increments) on OS. Results: Of 1260 women, 45.6% had upfront surgery, 54.4% had NAC, and 19.5% initiated treatment >90 days after BC diagnosis. Compared to the surgery group, more women in the NAC group had stage III BC (34.8% vs 81.5%). Living further away from a hospital and having hormone receptor positive (vs negative) BC was associated with longer TTI (8 additional days per 100 km, P = . 003 and 8 additional days, P = . 01, respectively), while Ki67 proliferation index >20 and upfront surgery (vs NAC) was associated with shorter TTI (12 and 9 days earlier; P = . 0001 and.007, respectively). Treatment initiation also differed among treating hospitals ( P < . 0001). Additional 30-day treatment delays were associated with worse survival in the surgery group (HR 1.11 [95%CI 1.003-1.22]), but not in the NAC group. Conclusions: Delays in BC treatment initiation are common in SA public hospitals and are associated with worse survival among women treated with upfront surgery. Abstract : This article examines how time to breast cancer treatment initiation affects overall survival in South African public hospitals.